KARAKTERISTIK PENDERITA ABORTUS INKOMPLETUS DI RSUD DR.PIRNGADI KOTA MEDAN TAHUN 2010 – 2011 - Rizqiana Halim; Sori Muda Sarumpaet; Hiswani . (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2013)
Abortion is an important public health problem. It’s often associated with maternal mortality in the form of bleeding complications (30%). The most common type of abortion is incomplete abortion. It should be addressed cause can make heavy bleeding and death. According to Panjaitan study in Martha Friska Hospital (2011), there were 105 cases of incomplete abortion from 175 cases of abortion. According to the data of Labuang Baji General Hospital (2012), there were 200 cases of incomplete abortion from 270 cases of abortion. To know the characteristics of incomplete abortion patients in Dr.Pirngadi General Hospital Medan in 2010 - 2011, conducted a study with case series design and total sampling for 100 patients. The highest proportion is 61% at low risk age group (20-35 years), 96% married, 59% senior high school, 69% a housewife, 56% Muslim, 78% in the city of Medan, 38% of gestational age 9 week, 54% multiparous, 70% miscarriage, 73% normal labor, 70% have a history of spontaneous abortion, 87% no history of the disease, 98% no complications, 94% curettage, The old patient care average is 2.23 days, and 59% healthy after treatment. The job by pregnancy history (housewife 70% had miscarried),age by  parity (p=0.001), parity by pregnancy history (p=0.042), parity by abortion history (p=0.042), medical management by circumstances after treatment (healthy 96,5% curettage), length of treatment by the average gestational age (5-10 weeks of 2.09 days, 11-16 days 4.14 weeks). Dr.Pirngadi General Hospital expected to increase quality of services, especially on incidence of incomplete abortion. The authorities expected to increase the health promotion and education of abortion on adolescents and adults as a preventive incidence of abortion, including incomplete abortion. Keywords: Characteristics,  Incomplete Abortion, Dr.Pirngadi General Hospital